Intervista a Danilo Prosperi, curatore di Polo Museale dell'Abruzzo 3D Project. I Capolavori dell'arte abruzzese in 3D e Virtual Tour dei principali Musei dell'Abruzzo. - Redazione Archeomatica (mediaGEO soc. coop., 2018)
The project, born from an idea of the Polo Museale dell'Abruzzo, in the person of the Director Dott.ssa Lucia Arbace, under the supervision of the RUP of the Project, Dr. Giulia Tortoriello, entrusted to ARCHIMETRIA Group, a team of professionals who work in the field of 3D documentation and technological innovation applied to cultural heritage, led by Arch. Danilo Prosperi, founder and CTO of the study, was born in July 2017 and ended in March 2018.